The Effect of Love of Money, Individual Morality, and Information Asymmetry on Fraud with Religiosity as A Moderating Variable - Putu Novi Anesya Dewi A.; Ni Putu Sri Harta Mimba; Ni Made Dwi Ratnadi; Ni Ketut Rasmini (Jurnal Ilmiah Akuntansi, 2026)
This study examines the effects of love of money, individual morality, and information asymmetry on fraud tendencies and investigates the moderating role of religiosity in these relationships. The study focuses on Village-Owned Enterprises in Karangasem Regency, Indonesia. Data were collected through questionnaires administered to 216 directors, secretaries, and treasurers from 72 Village-Owned Enterprises and analyzed using partial least squares structural equation modeling. The results show that love of money and information asymmetry are positively associated with fraud tendencies, whereas individual morality is negatively associated with fraud tendencies. Religiosity weakens the positive effects of love of money and information asymmetry on fraud tendencies and strengthens the negative effect of individual morality. These findings extend the fraud hexagon theory and the theory of planned behavior by demonstrating that religiosity functions as a contingency factor that shapes how individual dispositions and organizational information conditions are associated with fraud tendencies. The study also highlights the importance of combining internal control improvements with ethical and religious value reinforcement in the governance of Village-Owned Enterprises.